If the objective is herd immunity, on whom should it be built? - Christian Gollier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Assuming that there is no other solution than herd immunity in front of the current pandemic, on which categories of citizens should we build this herd immunity? Given the fact that young people face a mortality rate which is at least a thousand times smaller than people aged 70 years and more, there is a simple rational to build it on these younger generations. The transfer of some mortality risk to younger people raises dfficult ethical issues. However, none of the familiar moral or operational guidelines (equality of rights, VSL, QALY, ...) that have been used in the Western world over the last century weights the value of young lives 1000 times or more than the lives of the elders. This suggests that Society could offer Covid protection to the elders by conning them as long as this herd immunity has not been attained by the younger generations. This would be a potent demonstration of intergenerational solidarity towards the most vulnerable people in our community. The welfare gain of this age-specic deconfinement strategy is huge, as it can reduce the global death toll by more than 80%.
Keywords: 330; VSL; QALE; covid; pandemics; herd immunity; deconfinement